PERKEMBANGAN DAYA SAING EKSPOR RI-CHINA SELAMA PERIODE 1985-2010: SUATU PELAJARAN BAGI INDONESIA - Sabaruddin, Sulthon Sjahril (Buletin Studi Ekonomi; VOL.18.NO.2.AGUSTUS 2013. (PP 85-190), 2014)
Abstract: RI-China Export Competitivess Development during 1985-2010 : A Lesson for Indonesia This paper is intended to evaluate the development and changes in the structure of the Indonesian and China exports comparative advantage (the competitiveness of exports) during the period of 1985-2010. The results of the empirical analysis for the exports comparative advantage shows that during the period of 1985-2010, the trend of structure development of the competitiveness of Indonesian exports is now more diversified and become a country which previously an exporter-based of natural resource country, and now become a country in which the manufacturing sector played a bigger role to encourage the Indonesian exports with a relatively high competitiveness. On the other hand, China has undergone a huge industrial development at a faster pace compared Indonesian. Whereas in 1985, the top-ten products of China’s exports the majority originated from the primary sector, and now in 2010, China has successfully export the technological-based products, for instance, the engine data processors and telecommunication equipment with a very high level of competitiveness. Besides, China has also successfully encourage the export of highly competitive textile products, furniture, pedestal legs and toys child. China has now become one of the countries who has the technologicalbased industry with a very high competitiveness and as well a strong competitive manufacturing products.
Keywords: comparative advantage, the competitiveness of export, normalized revealed comparative advantage (NRCA), trade balance index (TBI), product mapping